Checklist of Moroccan aquatic beetles (Coleoptera: Hydraenidae Mulsant, 1844). New records and updates - Benamar, Loubna; Bennas, Nard; Hassoun, Mustapha; Millán, Andrés (Zootaxa, 2022)
Several field surveys at 391 freshwater localities between 1985 and 2019 were undertaken in Morocco. Altogether, our field studies identified 67 species belonging to three genera (Hydraena, Limnebius, and Ochthebius), and representing 85.89% of the Hydraenidae fauna of the country. The species Hydraena exarata Kiesenwetter, 1866 is reported for the first time from Africa, and Ochthebius (Ochthebius) thermalis Janssens, 1965 and O. (Ochthebius) grandipennis Fairmaire, 1879 are here recorded for the first time from Morocco. These findings increased the number of Moroccan Hydraenidae to 78. Ochthebius semisericeus Saint-Claire Deville, 1914 and O. viridis Peyron, 1858 are excluded from the Moroccan fauna. Furthermore, the checklist presented in this work includes 15 Moroccan endemic, 19 Ibero-Maghrebian endemic and 8 Maghrebian endemic species. A biogeographical analysis shows that the Hydraenidae from Morocco are essentially Mediterranean (89.74%), while the Palaearctic elements (7.70%) and the species with wider distributions (2.56%) are less represented, highlighting the general limited dispersion capability of Hydraenidae compared to other water beetle families. The present study can serve as the basis for future progress in the knowledge of the Moroccan Hydraenidae.